Continuity of Housing Expression based on the Elderly Bugis Culture - Putri Nur Sakinah; Arina Hayati; Muhammad Faqih (Universitas Udayana, 2023)
Elderly people tend to continue passing down cultural values to the next generation. The Bugis community from South Sulawesi has solid cultural values that relate to rules of life and living called